AN ARDUINO-CONTROLLED SMART SYSTEM FOR EFFICIENT CARPET MOISTURE REDUCTION - Narendra Ahmad (Khamdan Karya Cipta, 2025)
In various sectors, the increasing demand for efficiency and innovation has made the development of technology to address daily challenges highly relevant. This study aims to design and construct an automated and eco-friendly carpet dryer prototype controlled by an Arduino Mega 2560 microcontroller. The system is specifically engineered to overcome the common issue of slow and inefficient carpet drying, particularly in densely populated urban environments. The research methodology involves both hardware design and software development. The hardware components include heating elements, a fan motor, and sensors for detecting temperature and humidity. The software was developed using the C++ programming language. The drying process is initiated by a DHT11 sensor that detects carpet moisture levels. If the humidity surpasses a predefined threshold, the system automatically activates the heating element and fan to accelerate the evaporation process. Once the desired moisture level is reached, the system will automatically shut down. Experimental results indicate that the prototype effectively reduces carpet humidity. The use of Arduino as the central controller enables the system to operate autonomously and respond dynamically to environmental conditions. Furthermore, its compact and energy-efficient design positions this prototype as a viable and sustainable solution. This research demonstrates that microcontroller technology can be effectively applied to create practical, efficient, and automated solutions for daily life.